Risk Factors of Neonatal Jaundice Among Newborns Admitted in a Tertiary Care Centre of Western Nepal - Shrestha, Prapti; Devkota, Askal; Kunwar, Subarna; Ghimire, Mukti (Grande Medical Journal, 2025)
Background Neonatal hyperbilirubinemia remains a significant contributor to morbidity during the early days of life, particularly within the first week. Its underlying causes are often diverse and multifactorial. This study aimed to identify risk factors associated with neonatal hyperbilirubinemia and to explore the relationship between these factors and the severity of the condition in neonates admitted to a tertiary care center in western Nepal. Method An observational cross-sectional study was conducted at the Neonatal Intensive Care Unit (NICU) and Special Care Baby Unit (SCBU) of Lumbini Medical College from July 2017 to June 2018. Neonates aged 0–7 days admitted during this period were consecutively enrolled. Comprehensive clinical evaluations were performed, and relevant laboratory investigations were obtained. Data were analyzed using SPSS version 21. Result Among the 169 neonates enrolled, 129 (76.3%) were diagnosed with jaundice. Of these, 68% were full-term and 32% preterm. Most cases (78.3%) developed jaundice within the first three days of life, with the highest incidence observed on day two (47.3%), followed by day three (24.9%) and day four (12.4%). Male infants were more frequently affected. Conclusion This study underscores the prevalence of neonatal hyperbilirubinemia in the early neonatal period and highlights multiple associated risk factors. Prompt recognition and management are essential to reduce potential complications.